Simulation of Optical Frequency Comb Sources Using Electro Optical Modulators - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2021)
The theoretical basis of Optical Frequency Comb Sources (OFCS) using optical modulators is presented. The different classes of OFCSs and their main characteristics are shown. Experimental measurements and simulation results using Photo Design software are also presented, demonstrating the feasibility of generating optical frequency combs using phase modulators, with modulating frequencies in the order of GHz. © 2021 IEEE.